1998
DOI: 10.1002/(sici)1097-0142(19980501)82:9<1709::aid-cncr18>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of sex steroid receptors, cyclins, and cyclin-dependent kinases in the normal and neoplastic squamous epithelia of the uterine cervix

Abstract: METHODS.Immunohistochemical staining was performed on formalin fixed, parafShinshu University School of Medicine, Matsufin embedded tissue sections of normal squamous epithelia (30 cases), cervical moto, Japan.intraepithelial neoplasia (CIN) (21 cases), and invasive squamous carcinoma (SCC) (33 cases), using antibodies against estrogen receptors (ER), progesterone receptors (PR), cyclins (E, A, and B1), cyclin-dependent kinases (cdk2 and cdc2), and p53protein. In addition, growth activity of SCC was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
50
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 41 publications
10
50
1
Order By: Relevance
“…As outlined in Table 3, our cervical intraepithelial neoplasia 1 group did not show any phase-dependent variation in mitotic index that was markedly discordant with the other cervical intraepithelial neoplasia grades. Kanai et al, 23 in contrast, found that while ER was decreased in dysplastic epithelium, PR was increased. Thus, the precise mechanistic basis for this potential hormonal influence remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…As outlined in Table 3, our cervical intraepithelial neoplasia 1 group did not show any phase-dependent variation in mitotic index that was markedly discordant with the other cervical intraepithelial neoplasia grades. Kanai et al, 23 in contrast, found that while ER was decreased in dysplastic epithelium, PR was increased. Thus, the precise mechanistic basis for this potential hormonal influence remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…[20][21][22] Nonetheless, it has long been recognized that cervical squamous epithelial cells contain sex-steroid receptors and hence, their proliferation and differentiation are influenced, to some extent, by the menstrual cycle and/ or sex-steroid hormonal levels. [20][21][22][23][24][25][26][27][28] Most studies have localized ERs and progesterone receptors (PRs), at minimum, to the basal and parabasal cell layers of the normal ectocervix. [20][21][22][23][24][25][26][27][28] Data on a possible correlation between the localization and the extent of ERs and the menstrual cycle phase are less homogeneous.…”
mentioning
confidence: 99%
See 3 more Smart Citations